PERAN PENELITI DAN POLA KOORDINASI PENELITIAN DALAM RANGKA OPTIMALISASI FUNGSI PENELITIAN DALAM PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN - Ahyar Ari Gayo (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2017)
Law is an important component in a community. Development of society of course also be influential for the development of the law, thus the development of society would require a legal development that is in tune with the needs and development of the times. One of the components that play an important role in the development of the law is a legal researcher. The role of legal research in building the national legal system is very important to reveal the scientific data concerning aspects of philosophical, juridical, sociological, economic, and political, which can affect the development of the necessary legal Government of Indonesia as a development policy in the legal field. Researcher as implementers of development, especially in the field of law, in order to improve the effectiveness, efficiency, and optimize the necessary coordination at all levels both internal and external level ministry / agency. Researchers law, not only the need to coordinate with other researchers in the field of law only, but also need to coordinate with researchers in other fields as well as coordinate with other functional associated, in particular functional designer of law, because the creation of a legislation can not be monodicipliner done alone. The study, conducted by researchers aimed to formulate new legal norms that have been suggested by the study, and also formulate alternatives. The materials obtained from these studies can be used as input in the preparation of Academic Legislation of the bill to be drafted.Keyword: researcher, legal research, law making